Indicadores emocionais de estudantes universitários : um estudo quasi-experimental com Haṭha-Yoga - Leite, Vanessa Ferraz (2023)
Emotional indicators are variables that allow measuring reactions that relate basal and primary emotional aspects, such as fear, anger, sadness, and joy to more refined and profound affections, which can strengthen full attention, compassion, and self-compassion. Thus, due to its complexity, it requires an evaluation that considers biopsychosocial aspects. Objective: to evaluate the emotional indicators of undergraduate health care students, pre- and post-intervention with a Haṭha-Yoga program. Method: the main study, which responds to the general objective of the thesis, is a quasi-experimental study, developed between May and October 2022, with 32 health area students (nursing, nutrition, medicine and psychology courses) from a public university, divided into two groups: 14 in the intervention group and 18 in the control group. Before and after the intervention, the participants were evaluated with the Mindful Attention Awareness Scale (MAAS); Santa Clara Brief Compassion Scale (SCBCS); Self-Compassion Scale (SCS); Mini International Neuropsychiatric Interview (MINI); Depression, Anxiety, and Stress Scale (DASS-21); Barratt Impulsiveness Scale (BIS11); Epworth Sleepiness Scale (EPWORTH). Descriptive analyses and inferences were calculated using absolute and relative frequencies, mean and standard deviation, and paired ttest assessed the effect of intervention. The data generated in the pre-intervention collection, from 611 students from four health courses, originated an observational, correlational, and cross-sectional study with the objective of evaluating the association between indicators of emotional distress and dispositional mindfulness in health students from a Brazilian federal public university. In this study, the continuous variables were expressed by mean and standard deviation, the categorical variables by absolute and relative frequency, and multiple linear regression was used to analyze the factors associated with dispositional full attention. The analyses were carried out using SPSS software and the research complied with the current legislation about ethical aspects in both studies. Results: In the main study, there was an increase in the emotional indicators of compassion and self-compassion and a decrease in anxiety symptoms and daytime sleepiness after eight weeks of Haṭha-Yoga practice. In the control group there was a significant decrease in the dispositional full attention emotional indicator. The cross-sectional study revealed that among the 611 students evaluated, the majority were female, ≤ 22 years old, non-white, with a higher prevalence of medical students. Students showed moderate levels of dispositional full attention (x̅=51.75; standard deviation=12.67) and 52.2% had depressive symptoms, 73.3% anxiety symptoms, 38.7% stress symptomatology, 42.2% current suicide risk, and 55.5% excessive daytime sleepiness symptoms. In the regression analysis, the variables stress, depression and current suicide risk showed negative association with dispositional full attention ability. Conclusion: the practice of Haṭha-Yoga had a positive impact on students' emotional indicators, contributing to health promotion and self-care. Knowing the indicators of emotional distress that significantly reduce the potential of dispositional full attention can be useful as a situational diagnosis for better delineation of strategies that promote the emotional health care of health care students.